Cryptography in undergraduate education: perceptions of postgraduate students. Issue 6 (2nd November 2021) - Griffiths, Barry J.
Abstract: This paper uses a qualitative methodology to share the experience of students who have made the transition from being an undergraduate student to being a postgraduate student with a research focus on cryptography. In particular, it looks at the motivation of the participants to study cryptography, the training that they received as undergraduates, and how it can be improved. Twenty postgraduate students from fifteen different countries agreed to take part in the study. The data collected suggests that most postgraduate students chose to study cryptography during the second half of their undergraduate program, first gaining a broader knowledge of mathematics or computer science. They view the field as both important and exciting, but cite the value of a strong mathematical background, which could be enhanced by stronger undergraduate programing requirements. Most of the participants plan to stay in academia once their postgraduate program ends and offer a range of ideas to help promote the field of cryptography so that younger students are aware of it.